2016
DOI: 10.1111/apt.13865
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of faecal biomarkers in detecting colorectal cancer and adenoma in symptomatic patients

Abstract: SUMMARY BackgroundThe diagnosis of colorectal cancer (CRC) can be difficult as symptoms are variable with poor specificity. Thus, there is a quest for simple, non-invasive testing that can help streamline those with significant colonic pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
107
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 16 publications
(39 reference statements)
14
107
1
1
Order By: Relevance
“…Indeed, the presence of alarm symptoms, which raise the pre‐test probability of IBD, may be crucial to the successful application of calprotectin diagnostic pathways in primary care; without which the PPV of calprotectin may too low to be clinically useful in identifying IBD . Further research is required to establish how calprotectin will integrate with faecal immunochemical testing (FIT), in particular in older age‐groups than included here …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the presence of alarm symptoms, which raise the pre‐test probability of IBD, may be crucial to the successful application of calprotectin diagnostic pathways in primary care; without which the PPV of calprotectin may too low to be clinically useful in identifying IBD . Further research is required to establish how calprotectin will integrate with faecal immunochemical testing (FIT), in particular in older age‐groups than included here …”
Section: Discussionmentioning
confidence: 99%
“…21 Further research is required to establish how calprotectin will integrate with faecal immunochemical testing (FIT), in particular in older age-groups than included here. 20,[23][24][25] Our service evaluation demonstrates that faecal calprotectin is a clinically useful primary care test to distinguish IBD and organic intestinal disease as a whole from functional gut disorder in patients aged less than 46. However, simply introducing the pathway is not sufficient to either maximise gains, or guarantee its success.…”
Section: Implications For Future Practicementioning
confidence: 96%
“…For example, a FIT reading of less than 4 μg Hb/g faeces, with a colorectal cancer detection rate of 1⋅2 per cent, might prompt CT colonography instead of colonoscopy. This study excluded use of FIT in patients with rectal bleeding, but other studies have shown that undetectable blood on FIT has a reliable NPV 13,14 . However, exclusion of patients with rectal bleeding identifies a high-risk group with a PPV of 35⋅8 per cent for colorectal cancer and 53⋅7 per cent for significant bowel pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, new NICE guidance (NG12) that broadened referral criteria and aimed to ‘rule in’ more low‐risk patients by utilizing occult blood testing was seen as a double‐edged sword in many quarters. NG12 did not specify the type of occult blood testing that should be used; however, studies have suggested that faecal immunochemical testing (FIT) might be useful in symptomatic pathways and potentially more accurate than symptoms alone in predicting which patients need investigation for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Widlak et al stated that an undetectable FIT haemoglobin is sufficiently sensitive to exclude CRC, but they defined "undetectable" as f-Hb < 7 µg Hb/g faeces, the LoQ of the FIT system used. 38 The publications on FIT in the assessment of patients with symptoms clearly demonstrate the current controversy of which f-Hb cut-off to use and also the dilemma of how to report the results of FIT analyses. This has been addressed in detail recently 39 Many lower abdominal symptoms are transient, so it might be satisfactory to leave these patients without any immediate further investigation but, for others who continue to have symptoms, it is obligatory to have robust safety-netting procedures in place as recently described in a review of FIT in patients with symptoms, 41 including watching and waiting, referral to gastroenterology in secondary care, and perhaps a repeat FIT, although there is no evidence to date that this is useful.…”
Section: Selecting the Cut-off Faecal Haemoglobin Concentration (F-hbmentioning
confidence: 99%